Initiation of Chromosomal Replication in Predatory Bacterium Bdellovibrio bacteriovorus - Makowski, Łukasz; Donczew, Rafał; Weigel, Christoph; Zawilak-Pawlik, Anna; Zakrzewska-Czerwińska, Jolanta (Frontiers in Microbiology, 2016)
Bdellovibrio bacteriovorus is a small Gram-negative predatory bacterium that attacks other Gram-negative bacteria, including many animal, human, and plant pathogens. This bacterium exhibits a peculiar biphasic life cycle during which two different types of cells are produced: non-replicating highly motile cells (the free-living phase) and replicating cells (the intracellular-growth phase). The process of chromosomal replication in B. bacteriovorus must therefore be temporally and spatially regulated to ensure that it is coordinated with cell differentiation and cell cycle progression. Recently, B. bacteriovorus has received considerable research interest due to its intriguing life cycle and great potential as a prospective antimicrobial agent. Although we know that chromosomal replication in bacteria is mainly regulated at the initiation step, no data exists about this process in B. bacteriovorus. We report the first characterization of key elements of initiation of chromosomal replication – DnaA protein and oriC region from the predatory bacterium, B. bacteriovorus. In vitro studies using different approaches demonstrate that the B. bacteriovorus oriC (BdoriC) is specifically bound and unwound by the DnaA protein. Sequence comparison of the DnaA-binding sites enabled us to propose a consensus sequence for the B. bacteriovorus DnaA box (5’-NN(A/T)TCCACA-3’). Surprisingly, in vitro analysis revealed that BdoriC is also bound and unwound by the host DnaA proteins (relatively distantly related from B. bacteriovorus). We compared the architecture of the DnaA–oriC complexes (orisomes) in homologous (oriC and DnaA from B. bacteriovorus) and heterologous (BdoriC and DnaA from prey, E. coli or P. aeruginosa) systems. This work provides important new entry points toward improving our understanding of the initiation of chromosomal replication in this predatory bacterium.